Stratification in higher education : a comparative study - Shavit, Yossi [Herausgeber]; Arum, Richard [Herausgeber]; Gamoran, Adam [Herausgeber]; Menahem, Gila [Herausgeber] (Stanford Univ. Press, 2007)
"The mass expansion of higher education is one of the most important social transformations of the second half of the twentieth century. In this book, scholars from 15 countries, representing Western and Eastern Europe, East Asia, Israel, Australia, and the United States, assess the links between this expansion and inequality in the national context. Contrary to most expectations, the authors show that as access to higher education expands, all social classes benefit. Neither greater diversification nor privatization in higher education results in greater inequality. In some cases, especially where the most advantaged already have significant access to higher education, opportunities increase most for persons from disadvantaged origins. Also, during the late twentieth century, opportunities for women increased faster than those for men. Offering a new spin on conventional wisdom, this book shows how all social classes benefit from the expansion of higher education." (Publisher, BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; P 2.1.5 Fachhochschul- und Hochschulreife; T 4.5 Soziologie; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.1 Deutschland; I 2.3.4 Asien; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.2.2 Osteuropa; I 2.3.5 Australien, Ozeanien; Hochschulbildung; Hochschulzugang; Soziale Ungleichheit; Soziale Schichtung; Sozioökonomische Faktoren; Bildungsbeteiligung; Bildungsexpansion; Internationaler Vergleich; Bundesrepublik Deutschland; Israel; Japan; Südkorea; Schweden; Taiwan; USA; Großbritannien; Frankreich; Niederlande; Russland; Schweiz; Australien; Tschechische Republik; Italien